التنبؤ بالتلكؤ الأكاديمي بمعلومية التخطيط المستقبلي لدى طلاب كلية التربية جامعة الأزهر - طه، محمد فاروق محمد; إبراهيم، أحمد مهدي مصطفى; درويش، ناجي محمد حسن (جامعة الأزهر - كلية التربية, 2022)
هدف البحث الحالي إلى تحديد مدى اختلاف مستوى التلكؤ الأكاديمي (الإيجابي والسلبي) بسبب المرحلة الدراسية، وكذلك تحديد علاقة التلكؤ الأكاديمي (الإيجابي والسلبي) بالتخطيط المستقبلي، وتحديد إمكانية التنبؤ بالتلكؤ الأكاديمي (الإيجابي والسلبي) بمعلومية التخطيط المستقبلي، واستخدم في الدراسة المنهج الوصفي الارتباطي، وتم تطبيق مقياسي التلكؤ الأكاديمي (الإيجابي والسلبي) والتخطيط المستقبلي على المشاركين، وتكونت عينة البحث من (335) طالبا من طلاب الفرقتين الأولى والرابعة بكلية التربية للبنين بأسيوط- جامعة الأزهر، وأظهرت نتائج البحث وجود مستوى متوسط من التلكؤ الأكاديمي السلبي، ومستوى مرتفع التلكؤ الأكاديمي الإيجابي، ولم تظهر فروق دالة إحصائيا في التلكؤ الأكاديمي (الإيجابي والسلبي) لدى المشاركين تعود إلى المستوى التعليمي، بينما أظهرت النتائج وجود علاقة إيجابية بين التخطيط المستقبلي والتلكؤ الأكاديمي الإيجابي، ووجود علاقة عكسية بين التخطيط المستقبلي والتلكؤ الأكاديمي السلبي، وذلك لكل من (العينة الكلية للبحث، وعينة الفرقة الأولى، وعينة الفرقة الرابعة)، وأشارت النتائج إلى إمكانية التنبؤ إيجابيا بالتلكؤ الأكاديمي الإيجابي بمعلومية التخطيط المستقبلي، وإمكانية التنبؤ عكسيا بالتلكؤ الأكاديمي السلبي بمعلومية التخطيط المستقبلي، وذلك لكل من (العينة الكلية للبحث، وعينة الفرقة الأولى، وعينة الفرقة الرابعة). This study aimed to determine the extent to which there was a difference in academic procrastination due to students' academic level. The study investigated the correlation between academic procrastination and future planning, as well as the predictability of academic procrastination through future planning. The study utilized the correlation method and participants responded to the questionnaires of academic procrastination and future planning. The sample of the study consisted of (335) students from the first and fourth years students, Faculty of Education, Al-Azhar University in Assiut. Findings of the study revealed a moderate level of negative academic procrastination and high level of positive academic procrastination. Findings revealed that there were no statistically significant differences between the participants in academic procrastination (positive & negative) due to academic level. Results found a positive correlation between future planning and positive academic procrastination, while there was a negative correlation between future planning and negative academic procrastination in the (total sample, first year sample, fourth year sample). Results indicated the positive predictability of positive academic procrastination and the negative predictability of negative academic procrastination through future planning in the (total sample, first year sample, fourth year sample).
Keywords: المهام الأكاديمية -- التحصيل الدراسي -- التعليم الجامعي -- طلاب المرحلة الجامعية